Remote Sales Strategy for Early-Stage B2B SaaS Start-Up - Pivarník, Lukas (2023)
This thesis analyzes the sales strategy of early-stage pre-funding B2B SaaS start-ups with launched MVP; more specifically, the thesis focuses on outreach initiatives. The theoretical part discusses the steps, processes, and relevant elements of founder-led sales strategy in B2B SaaS start-ups, emphasizing sales development. The practical part utilizes the author’s start-up to analyze email, LinkedIn, and phone as sales development outreach channels and assess their effectiveness and time efficiency. Split tests were conducted within each channel to compare different messages. LinkedIn and phone outreach achieved stronger performance results in absolute terms. Regarding time efficiency, LinkedIn outreach requires considerably less time spent per conversion, followed by email and phone. Across all channels, messages emphasizing the benefits to the prospects yielded greater results than messages accenting pain point discovery efforts.